Studying the process of transformation of adult learners in a Second Chance School - Kesopoulos, Ioannis; Armaos, Remos (Adult Education Critical Issues, 2022)
The present study aims to examine the transformation of dysfunctional assumptions of adult learners in a Second Chance School (SCS) identifying the percentage of learners who perceive transformation, their profile, the fields of transformation and the factors, in and out of SCS. A mixed method study was conducted using the Learning Activities Survey (King, 2009), which comprises a questionnaire and an interview both of which were translated and adapted for the purposes of the current study. Twenty-five learners participated in the survey and 60% of them perceived any kind of transformation. Eight adult learners were further interviewed and six of them appeared to have transformed their previous assumptions in fields as the stereotypes and the social roles, the ability to improve their skills in lingual, numerical and computer literacy, the capability of comprehension of Greek language and processing their personal tasks (for the Muslim learners), the awareness οf their personal value and the ability to achieve personal targets. They also transformed the habit of mind for the importance of studies and their contribution to the self-consciousness and the reinforcement of learner’s self-confidence.